Unholy communion [videorecording (DVD)] - Coyle, Patrick (Film director); Bartley, Adam; Kartheiser, Vincent, 1979-; Flury, Iréna, 1984-; Robards, Laura; Rumreich, Thomas (Freestyle Digital Media, 2025)
A Minnesota cop uncovers priest murders tied to abuse and buried secrets in this gripping thriller based on Dr. Thomas Rumreich's novel.